Preparation of Magnetic Tubular Nanoreactors for Highly Efficient Catalysis - Yang, S.; Peng, L.; Cao, C.; Wei, F.; Liu, Jian; Zhu, Y.; Liu, C.; Wang, X.; Song, W. (Wiley - V C H Verlag GmbH & Co. KGaA, 2016)
© 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim We report an efficient and controllable route to prepare magnetic tubular nanoreactors composed of a mesoporous SiO2shell with iron-noble metal nanoparticles inside. The key of this method is to design and fabricate Fe nanoparticles encapsulated in a mesoporous SiO2shell. Making use of a galvanic replacement reaction between Fe and noble metal ions, all of the noble metal nanoparticles are loaded inside the mesoporous SiO2shell, and thus nanoreactors are formed. Taking Pd as an example, the prepared Pd-Fe@meso-SiO2tubular nanoreactor exhibits a high catalytic activity and excellent reusability for styrene hydrogenation under mild conditions. This study provides a facile route to fabricate magnetic nanoreactors with enhanced catalytic properties.